The Effect of The Audit Results of The Supreme Audit Board on The Financial Performance of Local Governments - Fitri Agustina; Ulfah Tika Saputri; Toni Nurhadianto; Yaumil Khoiriyah (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The purpose of this study was to examine the effect of the audit results of the Supreme Audit Board (BPK). It was consisted of audit opinion and audit findings on the financial performance of local governments from the economic ratios, effectiveness, and efficiency. The sample in this study used 15 regency/city governments in Lampung province. This study used a classic assumption test to meet Best Linear Unbiased Estimation (BLUE). This study used multiple linear regression to test the hypothesis. The result of this study indicated that audit opinion had no effect on economic and efficient financial performance but it had an effect on effective financial performance. In addition, audit findings had no effect on efficient and effective financial performance but it had an effect on economic-financial performanceKeywords : Audit Opinion, Audit Findings, Financial Performance of Local Governments